Caffeine facilitates extinction of auditory fear conditioning in rats - Takaaki Ozawa; Kodai Kaseda; Yukio Ichitani; Kazuo Yamada (Wiley, 2022)
Abstract Caffeine is the most widely consumed psychostimulant drug which could affect learning and memory acting through central adenosine receptors. Although caffeine has been suggested to impair the acquisition and the expression of auditory fear conditioning, its effect on the extinction has not been elucidated. To address this issue, in the present study, we investigated whether caffeine affects the extinction of conditioned fear in an auditory fear conditioning paradigm. During conditioning, rats received pairings of auditory cues (conditioned stimulus, CS) and foot shocks (unconditioned stimulus). On the next day, the rats were intraperitoneally administrated saline or caffeine (5 or 10 mg/kg) and then subjected to the extinction training, in which CSs were repeatedly presented without the foot shocks. Twenty‐four hours later, the rats were re‐exposed to the presentations of CSs (retrieval test). We found an acute caffeine administration dose‐dependently decreased freezing rates during the presentations of CS in the extinction training. Furthermore, caffeine‐treated animals showed lower conditioned freezing responses in the retrieval test. These findings suggest that caffeine facilitates the extinction of conditioned fear.